Enhanced Robotic Systems in Minimally Invasive Surgery - Khudair Abbas, Mohammad Taleb; ali hashim, Kamal Al-din hashim; Sahib Hamid, Hussein Mohammed; Saleh Awaid, Asmaa Munther (American Journal of Biology and Natural Sciences, 2024)
Minimally invasive surgery has been evolving rapidly since the beginning of the nineties, mainly due to the advent and continuous implementation of robotic systems. This paper reviews the main advancements achieved with the use of robotics by focusing on recently proposed and developing robotic systems specifically designed for minimally invasive surgery, indicating how the evolution of robotics is progressing. All the improvements offered by robotic systems are discussed in detail, beginning with the flexibility in the architecture of the last decade, which was tailored to accommodate instruments and manipulators for general minimal access surgery. [1][2][3].